1980
DOI: 10.1111/j.1471-4159.1980.tb11221.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of the Cytoplasmic Form of Brain Hexokinase in Cultured Astrocytes

Abstract: Astrocytes have been cultured from neonatal rat brain according to the flask culture procedure of Booher and Sensenbrenner. Approximately 80% of the hexokinase (ATP: D-hexose 6-phosphotransferase, EC 2.7.1.1) activity is found in the soluble fraction in homogenates of these cells, in contrast to only 20% of the total activity in the soluble fraction of whole brain homogenates. The hexokinase from the cultured astrocytes has been compared with the cytoplasmic and glucose-6-P-solubilized mitochondrial enzymes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
2
15
2
Order By: Relevance
“…It dges not seem likely that the relative distribution of hexokinase between cytoplasm and mitochondria can be directly correlated with cell type, i.e., neurons versus glia. Recently Roth-Schecter et al (1979) have reported that, in agreement with Lusk et al (1980), the predominant form of hexokinase in cultured astrocytes has a cytoplasmic location; addition of pentobarbital to the cultures, however, resulted in increased levels of hexokinase in the cells with the bulk of the increase seen in the mitochondrial-bound enzyme. Thus it would appear that, even in a given cell type, the relative distribution of hexokinase between cytoplasm and mitochondria may be influenced by environmental factors.…”
Section: J Kao-jen and J E Wilsonmentioning
confidence: 78%
See 2 more Smart Citations
“…It dges not seem likely that the relative distribution of hexokinase between cytoplasm and mitochondria can be directly correlated with cell type, i.e., neurons versus glia. Recently Roth-Schecter et al (1979) have reported that, in agreement with Lusk et al (1980), the predominant form of hexokinase in cultured astrocytes has a cytoplasmic location; addition of pentobarbital to the cultures, however, resulted in increased levels of hexokinase in the cells with the bulk of the increase seen in the mitochondrial-bound enzyme. Thus it would appear that, even in a given cell type, the relative distribution of hexokinase between cytoplasm and mitochondria may be influenced by environmental factors.…”
Section: J Kao-jen and J E Wilsonmentioning
confidence: 78%
“…In view of the marginal improvement from using the Vibratome and the considerably greater time requirement for preparing sections in this manner, we did not routinely use this method. modification of a method described previously (Lusk et al, 1980). All dilutions were prepared with 0.05 M-Tris-HCl buffer-0.9% NaCI, pH 7.6, containing 0.5% normal goat serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Astroglial cells express hexokinase I, the primary isoform of hexokinase found in brain. The early report on the predominance of soluble hexokinase in white matter of the cat brain (Bigl et al, 1971) corresponded well with the finding that in homogenates of cultured astrocytes about 80% of hexokinase activity was found in the soluble fraction (Lusk et al, 1980). However, in a recent study, astroglial cells were fixed with paraformaldehyde, incubated with monoclonal antibody against hexokinase I, and the localization of immunoreactivity was investigated with confocal laser microscopy (Lynch et al, 1991).…”
Section: Phosphorylation Of Carbohydrates By Astrocytesmentioning
confidence: 81%
“…However, no differentiation could be made between the hepatic and ␤-cell forms of this enzyme, since the PCR primers were specifically designed to cover a region homologous to both. This issue may be of some importance, because only hepatic GK expression is reduced by fasting and reinstated by refeeding (50). Such responsiveness to the metabolic state of the animal plays an important regulatory role in the expression of both pro-opiomelanocortin (POMC) and NPY in the ARC.…”
Section: Discussionmentioning
confidence: 99%